Aset Digital untuk Wakaf Produktif - Tuasikal, Muhammad Abduh (Fakultas Ekonomi Universitas Samudra, 2024)
The research examines Islamic law and formal law related to waqf with a focus on the potential of digital assets as productive waqf assets. So far, waqf research has mostly discussed movable and immovable objects, while digital assets, despite their great potential, are rarely discussed as mawquf (waqf assets). This research reviews the waqf rules on digital assets and how they can be utilised to fund social, educational, health, and religious programmes. Using the literature review method, the results show that digital assets, such as cryptocurrencies, NFTs, and digital documents, can be identified with certainty and provide sustainable benefits, making them suitable for productive waqf for the benefit of the ummah in the future.